The Effects of Government Regulation and Distinctive Capability on the Cost Leadership Strategy to Drive the Business Performance of Minimarket Chain - Hans Harischandra Tanuraharjo (Journal of Social Science, 2021)
The minimarket competition in Indonesia is very tight and dominated by the two largest minimarket chain, Indomaret and Alfamart. This study aims to examine the effects of government regulation and distinctive capability on the cost leadership strategy and its implications for the business performance of minimarket chain in Indonesia. It is based on empirical gap, not based on theoretical gap. The variables of distinctive capability and cost leadership strategy are relevant to the competitive advantage and sustainability. The method is explanatory survey, and the data is analyzed quantitatively on primary data. The unit of analysis is a minimarket chain in Indonesia. Time horizon is a cross section (one shoot). The populations are all minimarket chain companies in Indonesia which has the same set of characteristics amounted to 20. The analysis design used in this study is Partial Least Square. The coverage of samples under 100 respondents is very valid to use PLS. The results showed that cost leadership strategy dominantly was influenced by ownership of distinctive capability and was supported by government regulation. Cost leadership strategy has the most influence in directly increasing business performance. Government regulation and distinctive strategy can directly improve business performance, but the effect is smaller when compared to indirect effects through the cost leadership strategy. The findings of this study have implications for the management that efforts to improve business performance rely on the development of a cost leadership strategy, which is built on ownership of distinctive capability and adaptation of government regulation. Cost leadership strategy is suitable to be applied in this industry because of its hypercompetitive market structure. In addition, government regulations have a significant impact on the retail industry's strategy in Indonesia